CircRNA PLOD2 promotes tumorigenesis and Warburg effect in colon cancer by the miR-513a-5p/SIX1/LDHA axis. Issue 23 (2nd December 2022) - Li, Yingjia; Ma, Hongbing
ABSTRACT: Increasing evidence has proved that circRNAs might act as potential biomarkers for tumor diagnosis and prognosis. However, the functions and mechanisms of multiple circRNAs in colon cancer remains unclear. Here, we found circPLOD2 was dramatically upregulated in colon cancer tissue and cell lines. In vitro CCK-8, colony formation and transwell assays, and in vivo tumor transplantation assay were performed and explored that circPLOD2 might promote tumor proliferation, migration and invasion in vitro and in vivo. Moreover, based on the analysis of RNA pull-down, RNA immunoprecipitation, luciferase and rescued assays, we confirmed that the interactions between circPLOD2, miR-513a-5p and SIX1. It suggested that circPLOD2 acted as a sponge of miR-513a-5p to regulate the activation of the target gene SIX1. In addition, as a key transcription factor of Warburg effect related genes, SIX1 was proved to enhance the transcriptional expression of LDHA by chromatin immunoprecipitation assay, thereby regulating glycolysis in colon cancer cells. Therefore, we identified that circPLOD2 promoted colon cancer progression through miR-513a-5p/SIX1/LDHA axis, and acted as a new biomarker for colon cancer prognosis and treatment.